Human organ-specific autoimmune disease. Molecular cloning and expression of an autoantibody gene repertoire for a major autoantigen reveals an antigenic immunodominant region and restricted immunoglobulin gene usage in the target organ. - Chazenbalk, G D (1993)
The most common organ-specific autoimmune disease in humans involves the thyroid. Autoantibodies against thyroid peroxidase (TPO) are present in the sera of virtually all patients with active disease. We report the molecular cloning of the genes for 30 high-affinity, IgG-class human autoantibodies to TPO from thyroid-infiltrating B cells. Analysis of the putative germline genes used for the TPO human autoantibodies suggests the use of only five different H and L chain combinations involving four H chains and three L chains. In addition, the same combination of H and L chains was found in multiple patients. The F(ab) proteins expressed by these genes define two major, closely associated domains (A and B) in an immunodominant region on TPO. These A and B domains contain the binding sites of approximately 80% of IgG-class TPO autoantibodies in the sera of patients with autoimmune thyroid disease. The present information permits analysis, not previously possible, of the relationship between autoantibody H and L chain genes and the antigenic domains on an autoantigen. Our data, obtained using target organ-derived autoantibodies, indicate that there is restriction in H and L chain usage in relation to the interaction with specific antigenic domains in human, organ-specific autoimmune disease.